(untitled) (Práxis Educativa, 2025)
The work of Polish sociologist Zygmunt Bauman offers relevant insights for understanding contemporary global society. Consequently, the characteristics and concepts of his sociological approach have become objects of study and have been disseminated across various fields of knowledge. Thus, this article seeks to answer the following question: What are the potentialities of Zygmunt Bauman’s sociology as a foundation for research on Higher Education? The aim is to offer perspectives on possible uses of Bauman’s sociological hermeneutics as a basis for scientific investigations that take Higher Education as their object of study. This text adopts a qualitative–theoretical approach and uses bibliographic review as its methodological procedure. The study considers that Bauman’s sociological hermeneutics provides significant foundations for research in the field of Higher Education, particularly for studies that examine contextual aspects and conditioning factors of educational phenomena, as well as the principles, meanings and purposes of educational practice. Keywords: Zygmunt Bauman. Sociological hermeneutics. Higher Education.